Evaluation of the Efficacy of Novel Self Disinfectant Solution in Irreversible Hydrocolloid Impression Material - An Experimental Study - Sunantha Selvaraj; Alarmelu; Dorairaj Jayachandran; Shanmuga Priya (Indian Journal of Dental Research)
Background: Irreversible hydrocolloid materials are widely used for both diagnostic and definitive impression procedures. Impressions can be disinfected by immersion or spraying in any compatible disinfectant. Disinfectants should not adversely affect the dimensional stability of the impression and physical properties of impression material and subsequent dental cast. Objective: The study aims to evaluate the efficacy of a hypochlorous disinfectant solution mixed with irreversible hydrocolloid on setting time, antibacterial efficacy, and dimensional stability. Methodology: Three groups were made with one control group and three alginate impression was made for each participants in the maxillary arch with 24-hours intervals between one another using the same brand of commercially available chromatic alginate. The working and setting time were noted. Bacterial swabs were collected using a dry sterile cotton swab in the mid palatal region. Dental casts were made using type III gypsum. Result: The working and setting time had significant differences whereas the dimension among the cast has no significant difference. Microbial growth analysis had distinct differences among the groups. Conclusion: The self disinfection method using a pioneer solution of hypochlorous HOCl (100 ppm) to mix the alginate impression material rather than the water with the same powder-liquid ratio prescribed by the manufacturer had the same dimensional stability with improved antimicrobial action.